2018
DOI: 10.1155/2018/5762608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression among Prisoners in Jimma Town Prison, South West Ethiopia

Abstract: Background Mental disorder is one of the greatest challenges that current and future generations will face. Currently among all people suffering from depression, 85% of them live in low- and middle-income countries. Previous studies reported the global burden/prevalence of depression to be five to ten times higher among prisoners than the general population. However, the prevalence of depression among prisoners in our study area is not known. Objective This study therefore aimed to assess the prevalence and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
55
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(84 citation statements)
references
References 17 publications
17
55
11
1
Order By: Relevance
“…As evidenced in different studies, chronic medical illness is highly linked with depression resulting in poor prognosis and suicide [44][45][46]. Our study also revealed that those prisoners who have chronic medical illness have a higher odd to suffer from depression (AOR=2.51 CI:1.32,4.79) and this is in line with studies from Hawassa and Jimma prisons of Ethiopia [19,21].…”
Section: Predictors Of Depressionsupporting
confidence: 91%
See 1 more Smart Citation
“…As evidenced in different studies, chronic medical illness is highly linked with depression resulting in poor prognosis and suicide [44][45][46]. Our study also revealed that those prisoners who have chronic medical illness have a higher odd to suffer from depression (AOR=2.51 CI:1.32,4.79) and this is in line with studies from Hawassa and Jimma prisons of Ethiopia [19,21].…”
Section: Predictors Of Depressionsupporting
confidence: 91%
“…A cross-sectional study (n=355) in Hawassa Central Correctional Institution determined the prevalence of depression among prisoners by using the Patient Health Questionnaire (PHQ-9) is 56.4% [19]. Another most recent study from Ethiopia (Bahir Dar Prison) using the same tool (PHQ-9) revealed the prevalence of depression 45.5% [20] and a similar prevalence of depression is observed in Jimma Town Prison (41.9%) [21] and the prisons of Northwest Amhara, Ethiopia (43.8%) [22]. Different risk factors may result in depression such as gender and age; economic, educational, employment and marital status; disability, and poor social support; chronic medical illness (like, hypertension, epilepsy, HIV/AIDS); history of suicide, family history of psychiatric problems and exposure to violence and crime, and acculturation stress [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 95%
“…Another most recent study from Bahir Dar Prison, Ethiopia, using the same tool revealed a prevalence of 45.5% [22]. A similar prevalence of depression is observed in Jimma Town Prison [23] and the prison in Northwest Amhara [22], (i.e., 41.9% and 43.8%, respectively).…”
mentioning
confidence: 67%
“…Depression is the most common co‐occurring disorder with PTSD among trauma survivors (Briere & Scott, ). Abdu, Kabeta, Dube, Tessema, and Abera () found that 41.9% of prisoners reported clinical levels of depression on the Beck Depression Inventory–II. However, the DOJ provides more conservative estimates, ranging from 23% for state prisoners to 30% for jail inmates (James & Glaze, ).…”
Section: Relational Traumamentioning
confidence: 99%